2014
DOI: 10.1016/j.vetmic.2013.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Putative human and avian risk factors for avian influenza virus infections in backyard poultry in Egypt

Abstract: Highly pathogenic influenza A virus subtype H5N1 causes significant poultry mortality in the six countries where it is endemic and can also infect humans. Egypt has reported the third highest number of poultry outbreaks (n=1,084) globally. The objective of this cross-sectional study was to identify putative risk factors for H5N1 infections in backyard poultry in 16 villages in Damietta, El Gharbia, Fayoum, and Menofia governorates from 2010–2012. Cloacal and tracheal swabs and serum samples from domestic (n=12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…These actions in response to disease in poultry are similar to what has been observed in other African countries (Guèye 1999, Ekue et al 2002, Okeno et al 2012) although higher percentages of households selling sick poultry were reported in Ethiopia and Nigeria (Halima et al 2007, Paul et al 2012. Disposal of dead birds consisted mainly of taking carcasses to waste disposal areas of the village, a practice that has been shown to facilitate dissemination of HPAI virus H5N1 in Nigeria and Egypt (Musa et al 2013, Sheta et al 2014 …”
Section: Health Aspectssupporting
confidence: 75%
“…These actions in response to disease in poultry are similar to what has been observed in other African countries (Guèye 1999, Ekue et al 2002, Okeno et al 2012) although higher percentages of households selling sick poultry were reported in Ethiopia and Nigeria (Halima et al 2007, Paul et al 2012. Disposal of dead birds consisted mainly of taking carcasses to waste disposal areas of the village, a practice that has been shown to facilitate dissemination of HPAI virus H5N1 in Nigeria and Egypt (Musa et al 2013, Sheta et al 2014 …”
Section: Health Aspectssupporting
confidence: 75%
“…However, the integrated and highly organized production sectors (1 and 2) in Egypt have insufficient production capacities to meet these demands, and the shortfall Article has been met to date by the unorganized, unregistered and intricately concentrated small-scale poultry producers. These small-scale producers constitute the majority of sector 3 of broilers and layers, and possibly part of sector 4, and they are considered a high risk for poultry disease occurrence and transmission because they are constantly exposed to poultry pathogens due to low levels of compliance with instituted biosecurity measures (Sheta et al, 2014). After the first introduction of the virus in Egypt in 2006, a huge number of disease outbreaks were reported in commercial farms (n=848) and by March 2006, the reported highest number of disease notification rate per month has been obtained for the whole period of evaluation until 2016 ( Figure 4A, Table 1, Appendix 1).…”
Section: Discussionmentioning
confidence: 99%
“…This malpractice is considered as the strongest risk factor for transmission of HPAI in backyard flocks in Bangladesh (Biswas et al, 2009). In Egypt, significant correlation exists between disposal of poultry carcass and feces in the environment and HPAI infection in poultry (F = 15.7, P < 0.0001) (Sheta et al, 2014). In Ethiopia, scavenging behavior of backyard chickens and chicken dealers were considered a major risk factor for infecting the backyard flocks.…”
Section: Transmission Risk Of Pathogens In Backyard Flocks From Othermentioning
confidence: 99%